Ergonomic and Safety Experiences of Outdoor Gym Equipment Users - Merve Uca,; Selim Yıldız, (Journal of Educational Issues, 2024)
The number of outdoor gym equipment (OGE) installed in parks has increased to encourage physical activity and social interactions among city dwellers. However, little is known about perceptions of and experiences with OGE ergonomics and safety. Therefore, this study aims to reveal people’s ergonomic and safety experiences and perceptions about OGE. While the research universe consisted of individuals doing physical exercises in parks with OGE in Sakarya city, the sample was composed of a total of 359 people, 215 males and 144 females, selected using the convenience sampling method. The results showed that although the main purpose of the park-goers is not to use OGE, most of the participants thought that OGE use is not safe. Participants also reported that they had experienced various injuries while using OGE. Overall, although OGE seems to contribute to the healthy living needs of people, the relevant bodies may undertake improvements to increase their ergonomics and safety. In addition, it reveals the necessity of providing necessary trainings for the conscious use of OGE by users and having user quidebooks on OGE. Future research may reveal OGE-oriented behaviors and actual physical activity findings of OGE users. Finally, further research is encouraged to identify the health effects and safety-related issues of OGE.